The Spirituality and Psychological Resilience of Prophet Yusuf (AS) in Fī Ẓilāl al-Qur’ān: A Thematic Interpretation - Miftahul Khairi; Romlah Widayati; Samsul Ariyadi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The story of Prophet Yusuf (AS) in the Qur’an is one of the most systematic narratives depicting life’s trials—from betrayal and slander to authority. In the context of psychology, this narrative represents a profound model of spiritual resilience, relevant to contemporary mental health challenges. This study aims to analyze the aspect of spirituality in the story of Prophet Yusuf (AS) based on the interpretation of Fī Ẓilāl al-Qur’ān by Sayyid Qutb, systematically linked with the five resilience factors proposed by Connor and Davidson. The research employs a qualitative library-based method with a thematic (maudhu’i) tafsir approach and psychological resilience framework. The focus is on mapping spiritual values expressed in Surah Yusuf and exploring how they activate the other four resilience factors: personal competence, self-control, trust in intuition, and adaptability. The findings reveal that spirituality serves as the central foundation big77 of Prophet Yusuf’s resilience, providing meaning, guiding moral choices, and strengthening psychological endurance at every stage of trial. Sayyid Qutb’s interpretation highlights a deep spiritual connection with Allah as the core source of strength. The study concludes that integrating classical Qur’anic exegesis with modern psychological theory offers a new approach to understanding Qur’anic resilience. Its main contribution lies in enriching thematic Qur’anic interpretation through a psychospiritual lens and fostering interdisciplinary integration between revelation and contemporary psychology.